Ambiguities and Image Quality in Staggered SAR - Villano, Michelangelo; Krieger, Gerhard; Moreira, Alberto (Asia-Pacific Conference on Synthetic Aperture Radar (APSAR), 2015)
Staggered SAR is an innovative synthetic aperture radar (SAR) concept, where the pulse repetition interval (PRI) is continuously varied. This, together with digital beamforming (DBF) in elevation, allows high-resolution imaging of a wide continuous swath without the need for a long antenna with multiple azimuth apertures. As an additional benefit, the energy of range and azimuth ambiguities is spread over large areas: Ambiguities therefore appear in the image as a noise-like disturbance rather than localized artifacts. An analytical expression for the range-ambiguity-to-signal ratio (RASR) in staggered SAR is provided and a novel method for the estimation of the azimuth ambiguity-to-signal ratio (AASR) is proposed. A C-band design example based on a planar antenna is shown as well. The impact of staggered SAR operation on image quality is further assessed using highly oversampled F-SAR airborne data.
DLR Import::2019-04-03
Keywords: ambiguities; azimuth ambiguity-to-signal-ratio (AASR); high-resolution wide-swath (HRWS) imaging; range ambiguity-to-signal ratio (RASR); staggered SAR; Synthetic aperture radar (SAR); Tandem-L